2021
DOI: 10.3390/polym13040558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Magnetic Ferrocene-Containing Polymer with Photothermal Effects for Rapid Degradation of Methylene Blue

Abstract: Photothermal materials are attracting more and more attention. In this research, we synthesized a ferrocene-containing polymer with magnetism and photothermal properties. The resulting polymer was characterized by Fourier-transform infrared (FT-IR), vibrating sample magnetometer (VSM), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Its photo-thermocatalytic activity was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…After adding DMPO under Ar and O 2 , a new 4-line signal appears (1:2:2:1) due to the formation of a [DMPO-OH] • spin adduct, indicating the formation of a •OH radical. A previous report by Yu et al revealed that the hydroxyl radicals ( • OH) generation ability is favored in the ferrocene moieties under ambient reaction conditions. , It is well established that the ferrocene moieties are highly redox active and they can undergo a redox cycle to generate hydroxy radicals ( • OH). , Our study was further corroborated with the DFT computational analysis as evidenced later. …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…After adding DMPO under Ar and O 2 , a new 4-line signal appears (1:2:2:1) due to the formation of a [DMPO-OH] • spin adduct, indicating the formation of a •OH radical. A previous report by Yu et al revealed that the hydroxyl radicals ( • OH) generation ability is favored in the ferrocene moieties under ambient reaction conditions. , It is well established that the ferrocene moieties are highly redox active and they can undergo a redox cycle to generate hydroxy radicals ( • OH). , Our study was further corroborated with the DFT computational analysis as evidenced later. …”
Section: Resultssupporting
confidence: 86%
“…41,58 It is well established that the ferrocene moieties are highly redox active and they can undergo a redox cycle to generate hydroxy radicals ( • OH). 44,59 Our study was further corroborated with the DFT computational analysis as evidenced later. cyclohexenylperoxyl radical CHXO 2 • , which is followed by a hydrogen atom transfer from a CHX substrate via TS-3 giving cyclohexenyl hydroperoxide CHXO 2 H. The barrier of this Hatom transfer is calculated to be 21.3 kcal/mol relative to CHXO 2…”
Section: ■ Results and Discussionsupporting
confidence: 81%
“…On the other hand, researchers have also used ferrocene derivatives as ligands to construct porous organic framework materials through condensation and other reactions. Some of them successfully exhibited good catalytic activity in the photocatalytic degradation of pollutants such as Cr(VI) [5] and methylene blue [6] . And thanks to the strong interactions between Fe metal sites and gas molecules, porous organic polymers containing ferrocene achieved efficient adsorption of CO 2 gas [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the excellent properties of ferrocene moiety, it has been incorporated in the main chain or as a pendant group in the polymer backbone for a variety of applications such as electrical devices, photo-resistive semiconductors, ion sensing, energy storage devices, thermal and moisture resistant coatings, flame-retardant materials, etc. [ 19 , 20 , 21 , 22 , 23 ]. A combination of ferrocene moiety with flexible linkages in the backbone of polyamides has been widely used as a strategy to improve their processability along with their improved physiochemical properties [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%